2009
DOI: 10.1029/2008rg000265
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of thermally driven hydrological processes in partially saturated fractured rock

Abstract: [1] This paper is a review of the research that led to an indepth understanding of flow and transport processes under strong heat stimulation in fractured, porous rock. It first describes the anticipated multiple processes that come into play in a partially saturated, fractured porous volcanic tuff geological formation when it is subject to a heat source such as that originating from the decay of radionuclides. The rationale is then given for numerical modeling being a key element in the study of multiple proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 97 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…Heat transfer also plays a potentially important role in nuclear waste repositories: heat generated by radioactive waste can drive fluid flow [cf. Tsang et al , 2009], and CTRW could be applied to the (re)interpretation of heater tests around potential storage sites to provide insight into the limits of classical Fourier models in predicting future thermal perturbations. Our findings could also be directly employed in a novel CTRW‐based pore‐ to field‐scale upscaling approach for single‐phase solute transport [ Rhodes et al , 2008] where small‐scale simulations, like ours, are used to extract the relevant residence time distributions at a scale that is not resolved, for example, in a typical geothermal reservoir simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Heat transfer also plays a potentially important role in nuclear waste repositories: heat generated by radioactive waste can drive fluid flow [cf. Tsang et al , 2009], and CTRW could be applied to the (re)interpretation of heater tests around potential storage sites to provide insight into the limits of classical Fourier models in predicting future thermal perturbations. Our findings could also be directly employed in a novel CTRW‐based pore‐ to field‐scale upscaling approach for single‐phase solute transport [ Rhodes et al , 2008] where small‐scale simulations, like ours, are used to extract the relevant residence time distributions at a scale that is not resolved, for example, in a typical geothermal reservoir simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Tsang et al () reviewed the progress in another class of coupled phenomena, namely, coupled thermal‐hydrological processes relevant to long‐term storage of high heat generating radioactive wastes in Yucca Mountain, Nevada. The relevance of capillary barriers and above boiling temperatures to reducing seepage into the tunnels is emphasized.…”
Section: Possible Future Directions For Application Of Percolation Thmentioning
confidence: 99%
“…It is, however, also noted that cooling temperatures at later times can reverse the protective effect and increase the water infiltration along higher permeability zones. The problems discussed in the review by Tsang et al () are certainly amenable to solution using the methods of the present review, but the authors use numerical methods and standard constitutive relationships in the literature. As far as the applications of the concepts described in the present review is concerned, this class of problems remain wide open.…”
Section: Possible Future Directions For Application Of Percolation Thmentioning
confidence: 99%
“…Coupled THM behaviour of fractured rocks has been studied by several investigators and extensive references to this work can be found in areas related to geosciences and geomechanics (Noorishad et al, 1984;Selvadurai and Nguyen, 1995;Nguyen et al, 2005;Rutqvist et al, 2002;Guvanasen and Chan, 2000;Chan and Stanchell, 2008;Tsang et al, 2009). Thermohydro-mechanical processes in fractured rock formations can be analysed using two approaches: in the first approach, by modelling discrete fractures and specifying their locations within a host rock, which is modelled as a fracturefree medium; and in the second approach by introducing the influence of fractures implicitly through the derived overall constitutive equations for the fractured medium.…”
mentioning
confidence: 99%